FPGA implementation of RGB image encryption and decryption using DNA cryptography - Noorbasha, Fazal; Suresh, K (International Journal of Engineering and Technology, 2018)
The rapid growth in digitization transmission of information in the form of RGB image. During the process transmission of the image in a channel, some data may be degraded due to noise. At receiver side error in data has to be detected and corrected. Hamming code is one of the popular techniques for error detection and correction. In this paper new algorithm proposed for encryption and decryption of RGB image with DNA cryptography and hamming code for secure transmission, and correction. this algorithm first encodes data to hamming code and encrypted to DNA code. Two-bit error detection and correction for each pixel of the image can be performed.DNA code improves security and use of the Hamming code for error detection and correction. For the image of size 256*256 pixel image, it corrects up to 2*256*256 bits in RGB image. The RGB image encryption and decryption design using Verilog and implemented using FPGA (Field Programmable Gate Array).